Systematic position of Populus ciliata Wall. ex Royle on the study of shoot morphology and petiolar anatomy - Boris V. Proshkin; Andrey V. Klimov (Социально-экологические технологии, 2020)
Populus ciliate – ciliated poplar is distributed in the Himalayas at altitudes from 1300 to 3400 m above sea level, along river banks and wet slopes. The systematic position of the taxon remains unclear, although in most modern works it is attributed to the Tacamahaca section. The purpose of this study is to study the morphological features of crown shoots and the anatomical structure of petioles of Populus ciliata leaves to clarify its systematic position. Studies of the morphology of P. ciliata showed that it did not have specialized shortened shoots marking a section of balsamic poplars – diskoblasts. The most important signs of petiolar anatomy allowing the identification of poplar taxa at the section level are: the shape of the petiole cross section, the contours of its adaxial and abaxial sides, the shape of the rings of closed collateral bundles, the shape of the vascular system. A comparison of the obtained sections of P. ciliata with representatives of the Tacamahaca section indicates that the plants studied do not belong to balsamic poplars, since they differ in the absence of a groove pronounced on the adaxial side. The latter in the form of a small recess in the slice is fixed only at the place of its transition into the leaf blade. The contours of the abaxial and adaxial sides are round, the shape of the vascular system of the petiole is not highly arched like that of balsamic poplars, but linear, formed by elliptical rings of closed collateral bundles.